DETERMINAN MOTIVASI KERJA DAN PENGARUHNYA TERHADAP KINERJA KARYAWAN PT BANK MANDIRI (PERSERO) TBK CABANG BONTANG - Anggi Octavia Irawan; Zaki Baridwan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The purposes of this study is to examine the determinants of work motivation that affects the performance of the employees of PT Bank Mandiri Tbk branch Bontang. This study was the development of the research that has been conducted by Drake et al. (2007) and combine with Motivation-Hygiene Theory by Herzberg's. The research was conducted in three (3) branches of Bank Mandiri Bontang, East Kalimantan. The study used survey method in gather data. A total of 125 data can be processed using smartPLS. Study results show that feedback, rewards, recognition and work environment has a significant impact to work motivation and work motivation also has a significant impact to the performance of the employees of PT Bank Mandiri Tbk branch Bontang. Keywords: Employee performance, work motivation, feedback, reward, recognition and working conditions.